Intranasal M2SR (M2-Deficient Single Replication) H3N2 Influenza Vaccine Provides Enhanced Mucosal and Serum Antibodies in Adults. (9th November 2022) - Eiden, Joseph; Fierro, Carlos; Schwartz, Howard; Adams, Mark; Ellis, Kimberly J; Aitchison, Roger; Herber, Renee; Hatta, Yasuko; Marshall, David; Moser, Michael J; Belshe, Robert; Greenberg, Harry; et al.
Abstract: Background: We previously demonstrated that an intranasal dose of 10 8 50% tissue culture infectious dose (TCID50 ) M2-deficient single replication (M2SR) influenza vaccine protected against highly drifted H3N2 influenza challenge in a subset of subjects who demonstrated ≥2-fold increase in microneutralization (MN) antibodies to Belgium2015 (the challenge strain) after vaccination. Here, we describe a phase 1b, observer-blinded, dose-escalation study demonstrating an increased proportion of responders with this signal of immune protection. Methods: Serosusceptible subjects aged 18–49 years were randomized to receive 2 doses (10 8 –10 9 TCID50 ) of M2SR or placebo administered 28 days apart. Clinical specimens were collected before and after each dose. The primary objective was to demonstrate safety of M2SR vaccines. Results: The vaccine was well tolerated at all dose levels. Against Belgium2015, ≥ 2-fold increases in MN antibodies were noted among 40% (95% confidence interval [CI], 24.9%–56.7%) of subjects following a single 10 8 TCID50 M2SR dose and among 80.6% (95% CI, 61.4%–92.3%) after 10 9 dose ( P < .001). A single 10 9 TCID50 dose of M2SR generated ≥4-fold hemagglutination inhibition antibody seroconversion against the vaccine strain in 71% (95% CI, 52.0%–85.8%) of recipients. Mucosal and cellular immune responses were also induced. Conclusions: These results indicate that M2SR may provide substantial protection against infection with highly drifted strains of H3N2 influenza. Clinical Trials Registration: NCT03999554. Abstract : High dose of intranasal single replication M2SR influenza vaccine enhances mucosal and serum antibodies against drifted H3N2 influenza viruses. Serum microneutralization titer was shown to be a marker of protection against highly drifted H3N2 influenza in a previous challenge study. Lay Summary: In recent years, influenza A H3N2 viruses have evolved into multiple cocirculating clades, resulting in low vaccine efficacy and highlighting the need for more effective influenza vaccines. In a previous challenge study, a single intranasal dose of the investigational vaccine M2SR demonstrated protection against a highly drifted H3N2 influenza challenge virus in a subset of vaccine recipients with a signature immune response. Increasing the dose of the M2SR vaccine in this phase1b study demonstrated a statistically significant increase in the proportion of subjects with the signature immune responses seen previously. The vaccine-induced antibodies were cross-reactive with a panel of drifted H3N2 viruses from 2007 to 2019. Additionally, M2SR generated a rise in serum hemagglutination inhibition antibody titer in 71% of subjects. In contrast, the H3N2 seroresponse rate for the licensed intranasal vaccine FluMist is 10% in seronegative adults. Moreover, M2SR elicited mucosal and cell-mediated immune responses. This study demonstrates that the intranasal M2SR generates a multifaceted immune response and has the potential to provide better efficacy against vaccine-matched strains and influenza drift variants reducing the need to update the vaccine on an annual basis. This is a noteworthy step in the development of a broadly protective influenza vaccine.